Cardiac Radiofrequency Ablation Exacerbates Myocardial Injury through Pro-Inflammatory Response and Pro-Oxidative Stress in Elderly Patients with Persistent Atrial Fibrillation - Li, Xia; Zhou, Wenhang; Guo, Dianxuan; Hu, Youdong; Zhou, Hualan; Chen, Ying (Current Vascular Pharmacology, 2024)
Background: There is a need to assess myocardial damage after radiofrequency ablation of the pulmonary veins (PV) for persistent atrial fibrillation (PAF) in elderly patients. Objective: To evaluate oxidative stress, inflammatory response and myocardial damage in elderly patients with PAF after radiofrequency ablation of the PV. Methods: High-sensitivity troponin T (hsTnT), malondialdehyde-modified low-density lipoprotein (MDA-LDL), acrolein (ACR), lipid hydroperoxide (LHP), toll-like receptor 4 (TLR4), soluble growth stimulation expressed gene 2 (sST2), angiotensin II (Ang II) and myocardial blood flow (MBF) were determined before ablation and at 1, 3 and 5 months after radiofrequency ablation. Results: The levels of hsTnT, MDA-LDL, ACR, LHP, TLR4, sST2 and Ang II were increased 3 months after ablations compared with before ablation and 1 month after ablation, respectively (P<0.001); they were further increased at 5 months after ablation compared with the 1- and 3-month groups, respectively (P<0.001). MBF was decreased in the 3 months group after ablations compared with before ablation and 1-month after ablation, respectively (P<0.001), and was further decreased in 5-months after ablations compared with 1-month and 3-month groups, respectively (P<0.001). Patients with epicardial monopolar radiofrequency ablation had higher levels of hsTnT, MDA-LDL, ACR, LHP, TLR4, sST2, Ang II and lower MBF than patients with endocardial monopolar and bipolar radiofrequency ablations, respectively (P<0.001). Conclusion: Monopolar radiofrequency ablation method could result in more myocardial injury than bipolar radiofrequency ablation. Oxidative stress and inflammatory response may be involved in cardiac radiofrequency ablation-induced myocardial injury, resulting in myocardial ischemia in elderly patients with PAF.
Keywords: Radiofrequency ablation